Depot Location Problems By Considering Its Distribution Problems - Sartika, Henny; Gamal, Mohammad Daniel Hendri (Journal of Research in Mathematics Trends and Technology, 2019)
In this paper we study the problem of locating m depots to serve n customers in order to minimize the total transportation cost. The way the depots serve the customers is considered as a traveling salesperson problem. We combine the location and the traveling salesperson problem methods to find the near-optimal or the best depot locations. An illustrative example is presented to implement the proposed method.